Applications of Sliding Mode Control in Science and Engineering - Vaidyanathan, Sundarapandian; Lien, Chang-Hua.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Gathering 20 chapters contributed by respected experts, this book reports on the latest advances in and applications of sliding mode control in science and engineering. The respective chapters address applications of sliding mode control in the broad areas of chaos theory, robotics, electrical engineering, physics, chemical engineering, memristors, mechanical engineering, environmental engineering, finance, and biology. Special emphasis has been given to papers that offer practical solutions, and which examine design and modeling involving new types of sliding mode control such as higher order sliding mode control, terminal sliding mode control, super-twisting sliding mode control, and integral sliding mode control. This book serves as a unique reference guide to sliding mode control and its recent applications for graduate students and researchers with a basic knowledge of electrical and control systems engineering.
Sliding Mode Control Design for Some Classes of Chaotic Systems -- Sliding Mode Based Control and Synchronization of Chaotic Systems in Presence of Parametric Uncertainties -- Chattering Free Sliding Mode Controller Design for a Quadrotor Unmanned Aerial Vehicle -- Terminal Sliding Mode Controller Design for a Quadrotor Unmanned Aerial Vehicle -- Insensibility of the Second Order Sliding Mode Control via Measurement Noises: Application to a Robot Manipulator Surveillance Camera -- Robust Control of a Photovoltaic Battery System via Fuzzy Sliding Mode Approach -- Particle Swarm Optimization based Sliding Mode Control Design: Application to a Quadrotor Vehicle -- Global Stabilization of Nonlinear Systems via Novel Second Order Sliding Mode Control with an Application to a Novel Highly Chaotic System -- Complete Synchronization of Chaotic Systems via Novel Second Order Sliding Mode Control with an Application to a Novel Three-Scroll Chaotic System -- Novel Second-Order Sliding Mode Control Designfor the Anti-Synchronization of Chaotic Systems with an Application to a Novel Four-Wing Chaotic System -- Control and Synchronization of a Novel Hyperchaotic Two-Disk Dynamo System via Adaptive Integral Sliding Mode Control -- Adaptive Integral Sliding Mode Controller Design for the Control and Synchronization of a Rod-Type Plasma Torch Chaotic System -- Adaptive Integral Sliding Mode Controller Design for the Regulation and Synchronization of a Novel Hyperchaotic Finance System with a Stable Equilibrium -- Adaptive Integral Sliding Mode Controller Design for the Control of a Novel 6-D Coupled Double Convection Hyperchaotic System -- A Memristor-Based Hyperchaotic System with Hidden Attractor and its Sliding Mode Control -- Adaptive Integral Sliding Mode Control of a Chemical Chaotic Reactor System -- Adaptive Integral Sliding Mode Controller Design for the Control and Synchronization of a Novel Jerk Chaotic System -- Sliding Mode Control Design for a Sensorless Sun Tracker -- Super-Twisting Sliding Mode Control of the Enzymes-Substrates Biological Chaotic System -- Super-Twisting Sliding Mode Control and Synchronization of Moore-Spiegel Thermo-Mechanical Chaotic System.
Keywords: Computational intelligence; Control engineering; Nonlinear Optics; Computational Intelligence; Control and Systems Theory; Nonlinear Optics